The place of media power : pilgrims and witnesses of the media age - Couldry, Nick (Comedia., 2000)
![CDATA[This fascinating study focuses on an area neglected in previous studies of the media: the meetings between ordinary people and the media. Couldry explores what happens when people who normally consume the media witness media processes in action, or even become the object of media attention themselves.]].